PEMANFAATAN CANGKANG KEONG SAWAH SEBAGAI SUBSTITUSI SEBAHAGIAN SEMEN DAN AGREGAT HALUS TERHADAP KUAT TEKAN BETON - Munirul Hady; Bunyamin Bunyamin; Darwin Darwin; Aulia Rahman; Andrisman Satria (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2022)
AbstractConcrete is one of the choices as a structural material for construction in the construction sector, in this case, a concrete mixture is an object that is often used as research to obtain efficient construction methods and develop concrete constituent materials. The utilization of waste as a substitute for portland cement or additives is not a new thing. This research is expected to reduce rice snail waste that pollutes the environment and compare the compressive strength of normal concrete with concrete that uses rice snails as a partial substitute for cement and fine aggregate. This study refers to the ACI 211.1-91 and ASTM C-33/C33-08 methods. The rice snail waste was first crushed and filtered through a sieve that passed the ASTM No. 200 filter as a partial substitution of cement with substitution percentages of 0%, 5%, 10%, and 15% in the concrete mixture. The test object used is a cylinder with dimensions of 15 cm x 30 cm, totaling 40 specimens with a planned concrete quality of 17 MPa by the minimum requirements for structural concrete in SNI 2847-2019. Each percentage of 5 samples and testing will be carried out until the concrete is 28 days old in an immersion bath. The results show that the compressive strength using 0% snail shell variations was 17.35 MPa and 5%, 10%, and 15% variations were 15.74 MPa, 10.60 MPa, and 7.63 MPa. As well as the ratio of the density of the volume of concrete with mixed variations of 0%, 5%, 10% and 15%, namely 2344.4 kg/cm3, 2277.2 kg/cm3, 2170.4 kg/cm3 and 2103.7 kg/cm3. Keywords—Compressive Strength of Concrete, Rice Snail Waste, Substitution